Contribuição ao conhecimento fitoquímico, toxicológico e farmacológico de Banisteriopsis stellaris (Malpighiaceae) - Aragão, Mariana Costa (2024)
Banisteriopsis stellaris (Griseb.) B. Gates, commonly known as "marmelinha-da-flor branca," belongs to the Malpighiaceae family. The genus Banisteriopsis is notable within the family due to its production of important secondary metabolites, including alkaloids, flavonoids, and terpenoids, which exhibit various pharmacological effects with promising results. However, there is still limited evidence regarding its phytochemical and pharmacological potential. Therefore, this study aimed to contribute to the chemical and pharmacological knowledge of the species B. stellaris. Plant material was collected in April 2022 at Pico do Jabre (Matureia - PB) and identified by botanist Dr. Maria de Fátima Agra. A voucher specimen of the species was deposited in the Prof. Lauro Pires Xavier Herbarium of UFPB, under the number JPB 37874. The aerial parts were dried in an oven at 40°C, pulverized, and extracted with 95% ethanol, which was concentrated in a rotary evaporator to obtain the Crude Ethanol Extract (CEE). Subsequently, the CEE underwent Vacuum Liquid Chromatography (VLC) using different proportions and polarities of solvents, resulting in 9 extract fractions. An aliquot of 5 g of the ethyl acetate-methanol (AcOEt:MeOH) fraction (1:1) was subjected to column chromatography using Sephadex LH-20, resulting in 39 fractions. Fractions 22-27 were combined, totaling 875 mg, and subjected to Medium Pressure Liquid Chromatography (MPLC), yielding 15 fractions. Preparative High-Performance Liquid Chromatography (HPLC) methods were developed individually for fractions 08 and 10. Additionally, 673.0 mg of the chloroform fraction was subjected to column chromatography with silica gel, resulting in 10 fractions. For acute toxicity tests, mice received doses of 2000 and 5000 mg/kg of Banisteriopsis stellaris extract (CEE-Bs) orally and intraperitoneally. Regarding the genotoxicity assessment of CEE-Bs, the micronucleus test was conducted in mouse erythrocytes treated with CEE-Bs (2000 mg/kg p.o.) in a single dose. Anti-inflammatory tests were performed in mice treated with CEE-Bs (50, 100, or 200 mg/kg p.o.) using the paw edema and peritonitis models. The compounds were identified by NMR spectroscopy (uni and bidimensional) and compared with literature data, confirming the isolation of C-glycosylated flavonoids (orientin, vitexin, isovitexin, and isovitexin-2”-O-α-L-rhamnopyranoside) from the AcOEt:MeOH fraction. From fraction 04 of the chloroform phase, a mixture of the triterpenes α-amyrin, β-amyrin, and lupeol was isolated, all compounds being isolated for the first time in the species under study. Biological tests performed with CEE-Bs demonstrated its safety when administered orally, as there were no signs of acute toxicity or micronucleus alterations. The study results indicate that B. stellaris exhibited a significant anti-inflammatory response in the assays conducted at the observed doses, reducing edema and the exudation of inflammatory cells, with a reduction of 73.29% in edema, 66.71% in leukocyte migration, and 67.72% in neutrophil migration at a dose of 200 mg/kg of CEE. Therefore, this study highlights B. stellaris as a new source of biomolecules and its anti-inflammatory capacity, suggesting its utility in drug development. Future research can explore specific mechanisms and other pharmacological aspects of this species.